2014
DOI: 10.1103/physrevb.89.174430
|View full text |Cite|
|
Sign up to set email alerts
|

Spin transfer torque in antiferromagnetic spin valves: From clean to disordered regimes

Abstract: Current-driven spin torques in metallic spin valves composed of antiferromagnets are theoretically studied using the nonequilibrium Green's function method implemented on a tight-binding model. We focus our attention on G-type and L-type antiferromagnets in both clean and disordered regimes. In such structures, spin torques can either rotate the magnetic order parameter coherently (coherent torque) or compete with the internal antiferromagnetic exchange (exchange torque). We show that, depending on the symmetr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…G-type (checkerboard) and A-type (layered) antiferromagnets were considered and the case of the ferromagnetic spin valve is given for comparison. From Saidaoui, Manchon, and Waintal, 2014. In antiferromagnet/tunnel-barrier/antiferromagnet tunnel junctions, the symmetry of the torques is found to be the same as in metallic spin valves and their bias dependence is similar to that in ferromagnetic tunnel junctions (Saidaoui, Waintal, and Manchon, 2017) (Fig. 18).…”
Section: B Antiferromagnetic Tunnel Junctionsmentioning
confidence: 78%
See 2 more Smart Citations
“…G-type (checkerboard) and A-type (layered) antiferromagnets were considered and the case of the ferromagnetic spin valve is given for comparison. From Saidaoui, Manchon, and Waintal, 2014. In antiferromagnet/tunnel-barrier/antiferromagnet tunnel junctions, the symmetry of the torques is found to be the same as in metallic spin valves and their bias dependence is similar to that in ferromagnetic tunnel junctions (Saidaoui, Waintal, and Manchon, 2017) (Fig. 18).…”
Section: B Antiferromagnetic Tunnel Junctionsmentioning
confidence: 78%
“…In fact, in contrast to ferromagnetic spin valves, which are well described within incoherent semiclassical models, quantum coherence is crucial to enable the transmission of staggered spin density from one part of the spin valve to the other. Recent tight-binding calculations Saidaoui, Manchon, and Waintal, 2014) have indeed demonstrated that spin dephasing and mere spin-independent disorder in the spin valve dramatically quenches the spin torque efficiency (see Fig. 16).…”
Section: Principle Of Spin-transfer Torquementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, microscopic calculations showed that in these allantiferromagnetic spin valves, the non-relativistic STTs are subtle, spin-coherent quantum-interference phenomena relying on perfectly epitaxial and commensurate multilayers. 2,22,23 This may explain why the STT in antiferromagnetic spin valves has not yet been identified experimentally.…”
mentioning
confidence: 99%
“…22,23 By adding to the structure a second, free antiferromagnet with a commensurate lattice one can infer from the above considerations the symmtries of the STTs acting in the second antiferromagnet. Since p 1 = −p 2 is staggered in this case, the effective field ∼ s i ∼ M i × p i , driving the (anti)damping-like STT, is non-staggered and is therefore inefficient.…”
mentioning
confidence: 99%